Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

can you help me to solve this problem

g ( t ) = | t | - 3 ; find g ( 3 ) , g ( -5 ) , and g ( 0 )


Sagot :

Answer:

g(3) = 0. g(-5) = 2. g(0) = -3

Step-by-step explanation:

simply put whatever is inside the brackets, into where t is in the equation

e.g:

|t| - 3 for g(3) is: |3| - 3 = 0

the two lines around t just mean that whatever is inside you should always turn positive. so |-1| = 1 and |-3 + 1| = 2